Alternative management of irrigation water in crops of conilon - Bonomo, Diego Zancanella; Bonomo, Robson; Pezzopane, José Ricardo Macedo; Souza, Joabe Martins de (Coffee Science - ISSN 1984-3909, 2014)
The cultivation of Conilon coffee in North Capixaba has been done predominantly under irrigation due to the conditions of uneven distribution of rainfall. After the implementation of irrigation system management of irrigation water becomes very important economically and environmentally to the success of irrigation Conilon coffee. This study aimed to evaluate methods of water management in micro sprinkler irrigation system, used in coffee Conilon adults in the region of São Mateus (ES). For three seasons (2008 to 2011) the effects of irrigation management methods were evaluated for the water balance in the soil-plant atmosphere, tensiometry and system Irrigas in productive characteristics of four clones of coffee Conilon. The results indicated that the irrigation management system by Irrigas and water balance enabled the highest yields, but were those who had higher water consumption and less efficient use of irrigation water.